An exploratory study on current software development practices in Malaysia focusing on agile based software development - Mohamed, Shafinah Farvin Packeer; Baharom, Fauziah; Deraman, Aziz (Publications International, 2013)
Agile based software development has gained much interest among practitioners and researchers due its ability to produce high quality software in a shorter time of period. Even though its importance has been revealed, nevertheless, only few studies were conducted regarding its current practices in Malaysian software industry.Thus, a survey was conducted to study the practices and perception on the agile based software development in real-world projects.This paper discusses on the findings from the study.Structured questionnaire was used for data collection purpose.For data analysis, simple statistical methods were used which are frequency and cross tabulation. Outcome from this study reveals that agile based software development practices are important to produce high quality software. Thus, it prolonged to the needs of incorporating agile based software development practices as the reference standard in the process based software certification model which will be proposed.